2001
DOI: 10.1136/gut.48.4.542
|View full text |Cite
|
Sign up to set email alerts
|

Expression and penetrance of the hereditary pancreatitis phenotype in monozygotic twins

Abstract: Background-Hereditary pancreatitis (HP) is a rare autosomal dominant disorder with variable expression and an overall lifetime penetrance of 80%. We hypothesised that (1) monozygotic twins within similar environments would develop the typical signs of HP at a similar age, and (2) if penetrance were due to modifier genes or environment, all twin pairs would be concordant for expression of HP. Aim-Identify monozygotic twins with HP and determine the penetrance, concordance, and age of onset of symptoms. Methods-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…The cause of this incomplete penetrance is uncertain. In addition to further genetic factors, smoking, alcohol consumption, or the lack of antioxidants were assumed as manifestation factors [Sibert, 1978;Sossenheimer et al, 1997;Amann et al, 2001;Keim et al, 2001]. On the basis of a study of 60 affected and 25 nonaffected persons carrying the PRSS1 mutations N29I or R122H, we suggested that the TNFa-238A promoter variant could be a relevant manifestation factor for chronic pancreatitis in hereditary pancreatitis-families.…”
Section: Prss1 Mutations and Incomplete Penetrance Of Chronic Pancreamentioning
confidence: 89%
“…The cause of this incomplete penetrance is uncertain. In addition to further genetic factors, smoking, alcohol consumption, or the lack of antioxidants were assumed as manifestation factors [Sibert, 1978;Sossenheimer et al, 1997;Amann et al, 2001;Keim et al, 2001]. On the basis of a study of 60 affected and 25 nonaffected persons carrying the PRSS1 mutations N29I or R122H, we suggested that the TNFa-238A promoter variant could be a relevant manifestation factor for chronic pancreatitis in hereditary pancreatitis-families.…”
Section: Prss1 Mutations and Incomplete Penetrance Of Chronic Pancreamentioning
confidence: 89%
“…The penetrance of cationic trypsinogen gene mutations remains at approximately 80 % in the majority of studies. To investigate factors contributing to this, a study of monozygotic twins with HP was carried out [17] . Of 11 sets of twins, seven were suitable for this study.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Indeed, there must be other genetic, epigenetic or environmental factors that are critical in protecting the pancreas of these individuals. Studies on identical twins and specific investigations of obligate carriers have emphasized this fact without bringing any clear answers [29]. Additional questions surround the families that have been thoroughly investigated and all known mutations excluded [10].…”
Section: Hereditary Pancreatitismentioning
confidence: 99%